1982
DOI: 10.1111/j.1365-2672.1982.tb04685.x
|View full text |Cite
|
Sign up to set email alerts
|

Deoxyribonucleic acid homologies among strains of Bacteroides melaninogenicus and related species

Abstract: Saccharolytic, black‐pigmented Bacteroides strains, which at present belong to the species Bacteroides melaninogenicus were classified on the basis of deoxyribonucleic acid (DNA) base ratios and DNA hybridization studies. These strains were divided into several DNA homology groups, which showed no or low mutual DNA homology. A DNA homology group with a percentage guanine plus cytosine (G + C) of 42–43% was formed by three strains of Bact. melaninogenicus subsp. melaninogenicus; the type strain of this subspeci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1983
1983
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The two strains selected for use as DNA probes in this study have been shown previously to represent at least two centers of variation among strains labeled Prevotella intermedia (7,27). In the previous studies, reciprocal hybridizations between members of the two groups of isolates revealed approximately 40% DNA-DNA homology, perhaps because of the lower stringency of the reassociation experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two strains selected for use as DNA probes in this study have been shown previously to represent at least two centers of variation among strains labeled Prevotella intermedia (7,27). In the previous studies, reciprocal hybridizations between members of the two groups of isolates revealed approximately 40% DNA-DNA homology, perhaps because of the lower stringency of the reassociation experiments.…”
Section: Resultsmentioning
confidence: 99%
“…1) and therefore provided a rapid way to identify unknown isolates. The identification of two DNA homology groups among human Prevotella intermedia isolates has been reported previously (7,27). These isolates have been subdivided into three serotypes, serotypes I, 11, and 111, by using monoclonal antibodies (4).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the group of black-pigmented Bacteroides strains is very heterogeneous on the basis of DNA base contents and DNA hybridization studies. Therefore, reciassification has been proposed by several authors (van Steenbergen, de Soet & de Graaff 1979, Coykendall, Kaczmarek & Slots 1980,, van Steenbergen, Vlaanderen & de Graaff 1981, van Steenbergen. Vlaanderen & de Graaff 1982b.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to better classify this bacterial group have been made on the bases of physiologic characteristics (10), electrophoretic patterns of dehydrogenases (34), cellular fatty acid and sugar composition (3,4,18), lipid analysis (19,26), serology (15), and bacteriophage typing (2). The diversity of this bacterial group was further demonstrated in studies using 16S rRNA oligonucleotide cataloging (25), rRNA-DNA hybridization (12), DNA homology (11,36), and 5S rRNA comparative analysis (35). On the basis of this heterogeneity, Shah and Collins (30)(31)(32) proposed that the genus Bacteroides be divided into the following three genera: (i) Bacteroides sensu stricto, consisting of saccharolytic, nonpigmenting species such as the type species, B. fragilis, and its relatives; (ii) Prevotella, consisting of moderately saccharolytic, bile-sensitive, predominantly oral species, such as P. melaninogenica and P. intermedia; and (iii) Porphyromonas, generally consisting of asaccharolytic, black- L16484 L16489 L16486 M58762 M86695b L16495 L16493 L16494 L16497 L16496 L16490 L26102 L16491 L16492 L26103 L16475 L16477 L16478 L16476 L16465 L16467 L16466 L16483 L16487 L16468 L16481 L16469 L16470 L16471 L16479 L16480 L16474 L16472 L16482 L16473 L16488 L16498 (16).…”
mentioning
confidence: 99%